OPTIMALISASI PRAKTIKUM TITRASI ASAM BASA MELALUI INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN NILAI LAPORAN - Linda Ardianti, Dewi; Suryaningsih, Siti; Janatun, Tuti (ALOTROP, 2025)
Students generally have difficulty understanding chemistry learning material on acid-base titrations. Learning is still teacher-centered and there is little student activity in playing a role in the learning process. Objective: to discover science process skills and the value of guided inquiry-based acid-base titration practical reports. Method: quantitative descriptive, class XI MIPA 1 MAN 11 South Jakarta. The sample was 34 students using purposive random sampling. Data were collected using a 23-item questionnaire from indicators of science process skills in practical acid-base titration material and practical report grades. Research results: the implementation of guided inquiry-based acid-base titration practical learning showed good results. The average final score for students' practicum report results was 86.941, the standard deviation was 4.313. This indicates that the Minimum Completeness Criteria (KKM) set by the school of 80 has been achieved. The highest percentage of science process skills in the observing indicator is 82.6%. And the indicators of grouping, predicting, hypothesizing, applying concepts, interpreting, planning experiments, and using tools are categorized as good. Meanwhile, 2 other indicators are in the sufficient category, namely the indicator of asking questions 53.8% and communicating 60.6%. Conclusion: An acid-base titration practicum using the guided inquiry learning model can improve learning outcomes and develop students' science process skills. Keywords: Guided Inquiry; Science Process Skills; Practicum Report Value; Practicum.